2023
DOI: 10.3390/ma16247634
|View full text |Cite
|
Sign up to set email alerts
|

Critical Insight into Pretransitional Behavior and Dielectric Tunability of Relaxor Ceramics

Sylwester J. Rzoska,
Aleksandra Drozd-Rzoska,
Weronika Bulejak
et al.

Abstract: This model discussion focuses on links between the unique properties of relaxor ceramics and the basics of Critical Phenomena Physics and Glass Transition Physics. It indicates the significance of uniaxiality for the appearance of mean-field type features near the paraelectric-to-ferroelectric phase transition. Pretransitional fluctuations, that are increasing up to the size of a grain and leading to inter-grain, random, local electric fields are responsible for relaxor ceramics characteristics. Their impact y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 93 publications
0
10
0
Order By: Relevance
“…( 9 ) is worth stressing. It resembles the critical-like behavior in constrained system complex systems, for instance, in critical phenomena physics within the so-called Griffiths model 107 109 . For the parameters that can be derived from the results presented in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…( 9 ) is worth stressing. It resembles the critical-like behavior in constrained system complex systems, for instance, in critical phenomena physics within the so-called Griffiths model 107 109 . For the parameters that can be derived from the results presented in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…For instance, it occurs in the paraelectric phase, where order parameter changes (polarization) can be tested concerning the coupled field parameter (electric field in the given case). Such behavior is explained within the Clausius–Mossotti local field model, generally valid for systems composed of non-interacting and weakly interacting dipole moments, including their ‘immersion’ in a mean-field surrounding [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Experimental dielectric studies of liquids under nano-constraints showed that they can mimic the behavior under quasi-negative pressure conditions [ 77 , 78 , 79 , 80 ], i.e., the ‘rarefication’ (isotropic stretching), which has to weaken intermolecular and inter-dipolar interactions.…”
Section: Resultsmentioning
confidence: 99%
“…Such behavior is explained within the Clausius–Mossotti local field model, generally valid for systems composed of non-interacting and weakly interacting dipole moments, including their ‘immersion’ in a mean-field surrounding [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 ]. Experimental dielectric studies of liquids under nano-constraints showed that they can mimic the behavior under quasi-negative pressure conditions [ 77 , 78 , 79 , 80 ], i.e., the ‘rarefication’ (isotropic stretching), which has to weaken intermolecular and inter-dipolar interactions. Such nano-constrained conditions can be essential for quasi-liquid nano-layers in the solid-state pre-melting domain.…”
Section: Resultsmentioning
confidence: 99%
“…It resembles the critical-like behavior in constrained system complex systems, for instance, considered in physics within the so-called Griffiths model. [107][108][109] For the parameters that can be derived from the results presented in Fig. 3, the following relation approximates global population changes in Industrial Revolutions period:…”
Section: Figurementioning
confidence: 99%